2016
DOI: 10.1111/ggi.12869
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between intramuscular fat, muscle strength and gait independence in older women: A cross‐sectional study

Abstract: The present results suggest negative relationships between intramuscular fat and muscle strength, and intramuscular fat and degree of gait independence in dependent older women. In addition, dependent older women have more intramuscular fat than healthy older women. Geriatr Gerontol Int 2017; 17: 1683-1688.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(105 citation statements)
references
References 30 publications
3
101
0
1
Order By: Relevance
“…However, it was reported that obesity and aging are responsible for intramuscular fat accumulation in skeletal muscle tissue (22,23). Therefore, in patients with higher BMI, larger muscle mass results from both an increase of lean mass and deposition of intramuscular fat (24). Nevertheless, this does not represent a contraindication to the use of a gracilis muscle flap in reconstructive surgery in those cases where it is used to repair a soft-tissue defect without functional reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was reported that obesity and aging are responsible for intramuscular fat accumulation in skeletal muscle tissue (22,23). Therefore, in patients with higher BMI, larger muscle mass results from both an increase of lean mass and deposition of intramuscular fat (24). Nevertheless, this does not represent a contraindication to the use of a gracilis muscle flap in reconstructive surgery in those cases where it is used to repair a soft-tissue defect without functional reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this does not represent a contraindication to the use of a gracilis muscle flap in reconstructive surgery in those cases where it is used to repair a soft-tissue defect without functional reconstruction. Conversely, in situations when functional reconstruction is expected, care should be taken in the selection of this reconstructive option as intramuscular fat deposition results in reduced muscle quality and force (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[53][54][55][56] These results were replicated by other researchers as well, but they also evaluated the functional capacity of the subjects including gait speed and the sit-to-stand test that had a moderate correlation with EI. 27,48,[57][58][59] This findings make these few studies very interesting in terms of possible tools for the identification of sarcopenia and muscle quality because comprehensive assessment of physical function in older age is a better predictor of survival and other outcomes than the presence of disease or the extent of comorbidities. 60 Regarding diagnostic accuracy, only one publication has tested ROC curves for EI and found AUC of 0.66 for both men and women.…”
Section: Echo Intensitymentioning
confidence: 99%
“…53 Intramuscular fat increases with aging and is significantly higher among the elderly population. 54,55 It has a negative correlation with muscle strength and muscle function 56,57 and is an important factor in sarcopenia progression. Muscle and adipose tissues have different SoS times (1440 m/s for adipose tissue; 1585 m/s for muscle).…”
Section: Speed Of Sound Ultrasoundmentioning
confidence: 99%